Anthrax immune globulin improves hemodynamics and survival during B. anthracis toxin-induced shock in canines receiving titrated fluid and vasopressor support - Suffredini, Dante A. (Intensive Care Med Exp, 2017)
BACKGROUND: Although anthrax immune globulin (AIG) improved survival in antibiotic-treated Bacillus anthracis-challenged animal models, whether it adds to the benefit of conventional hemodynamic support for B. anthracis toxin-associated shock is unknown. METHODS: We therefore tested AIG in sedated, mechanically ventilated canines challenged with 24-h B. anthracis lethal and edema toxin infusions and supported for 96 h with a previously demonstrated protective regimen of titrated normal saline and norepinephrine. RESULTS: Compared to controls, proportional survival (%) was increased with AIG treatment started 4 h before (33 vs. 100%, n = 6 each) or 2 h (17 vs. 86%, n = 6 and 7 respectively) or 5 h (0 vs. 67%, n = 3 each) after the start of toxin (p ≤ 0.05) and overall [3 survivors of 15 controls (20%) vs. 14 of 16 AIG animals (88%); p = 0.006]. Averaged across treatment times, AIG increased blood pressure at 48 h and decreased norepinephrine requirements at 72 h (p ≤ 0.02), increased left ventricular ejection fraction at 48 and 72 h (p ≤ 0.02), and increased urine output and decreased net fluid balance at 72 and 96 h (p ≤ 0.04). AIG also reduced acidosis and renal and hepatic injury markers between 24 and 96 h. CONCLUSIONS: These findings further support AIG’s potential benefit for patients with B. anthracis infection and developing toxin-associated shock. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40635-017-0159-9) contains supplementary material, which is available to authorized users.